2019
DOI: 10.1007/s10620-019-05602-w
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating Elimination Diets: Controversies Regarding Dietary Treatment of Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EoE) is an immune-mediated disease triggered by food antigens for which dietary elimination treatment can induce and sustain histologic remission. Our review aims to describe the state-of-the-art regarding dietary treatment of EoE, highlighting a number of areas of controversy related to dietary therapy in EoE, including novel modalities for determining food triggers, making the empiric dietary elimination process more efficient, issues of crosscontamination and "dosing" of how much f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 81 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…Skin allergy tests are less effective and are not generally recommended but empiric eliminations are more effective and easier to follow. Nevertheless, long-term efficacy and adherence should be investigated further regardless of the chosen approach, also in comparison with pharmacological treatment [ 116 , 117 ].…”
Section: Therapy Of Eosinophilic Esophagitismentioning
confidence: 99%
“…Skin allergy tests are less effective and are not generally recommended but empiric eliminations are more effective and easier to follow. Nevertheless, long-term efficacy and adherence should be investigated further regardless of the chosen approach, also in comparison with pharmacological treatment [ 116 , 117 ].…”
Section: Therapy Of Eosinophilic Esophagitismentioning
confidence: 99%
“…A 4-food elimination diet eliminating dairy, wheat, egg, and soy/legumes has been shown to be effective in 54% to 64%. 56 Because milk frequently represents the culprit food in children with EoE, cow's milk elimination attempts have been made. Recently, a randomized controlled trial in 63 children has shown similar histologic remission rates for milk elimination compared with a 4-food elimination.…”
Section: New Dietary Approachesmentioning
confidence: 99%
“…23 Elimination diet avoiding food triggers is the only therapy targeting the cause of the disease, but the efficacy remains controversial, because none of the currently available allergy tests can adequately predict food allergens for EoE. 24 Up to 50% of patients diagnosed with EoE also had atopic dermatitis, 25 and EoGEC in Japan associated with atopic diseases. 11 While EoE can be considered as an involvement of allergic march in childhood, 26,27 the true prevalence of EoE and EoGEC in patients with atopic dermatitis remains to be determined.…”
Section: Gi Involvement In Atopic Dermatitismentioning
confidence: 99%
“…Whole‐genome mRNA expression analysis on tissue specimens from patients with EoE, AD and AA indicated a greater involvement of the IL‐13‐driven molecular pathways in EoE than AA or AD, and a significantly higher overlap of EoE with AD than with AA 23 . Elimination diet avoiding food triggers is the only therapy targeting the cause of the disease, but the efficacy remains controversial, because none of the currently available allergy tests can adequately predict food allergens for EoE 24 …”
Section: Gi Involvement In Atopic Dermatitismentioning
confidence: 99%